2009
DOI: 10.1089/ast.2009.0348
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Astrobiology Research and Teaching Activities Within the United Kingdom

Abstract: While astrobiology is apparently growing steadily around the world, in terms of the number of researchers drawn into this interdisciplinary area and teaching courses provided for new students, there have been very few studies conducted to chart this expansion quantitatively. To address this deficiency, the Astrobiology Society of Britain (ASB) conducted a questionnaire survey of universities and research institutions nationwide to ascertain the current extent of astrobiology research and teaching in the UK. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…A recent paper (Dartnell and Burchell 2009) in the journal Astrobiology sets out to try to answer some of these questions. And how widespread is such work in this country?…”
Section: Panspermia and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper (Dartnell and Burchell 2009) in the journal Astrobiology sets out to try to answer some of these questions. And how widespread is such work in this country?…”
Section: Panspermia and Beyondmentioning
confidence: 99%
“…The results of a recent survey of UK activities in astrobiology is about to be published in the journal Astrobiology (Dartnell and Burchell 2009) and reveals a wide ranging and deeply rooted UK community in the field. The focus of ESA's planetary missions on the Aurora theme leading to Mars (focusing on ExoMars in the near future and an eventual Mars sample return mission) has helped this, but in parallel a whole wide range of other activities in research and teaching are underway in the UK.…”
mentioning
confidence: 99%
“…A survey on astrobiology research and teaching activities within the UK conducted in 2007/08 by use of a questionnaire distributed to members of British astrobiology groups (e.g., Astrobiology Society of Britain, UK Planetary Form and Astrosurf Network) showed that astrobiology had already achieved a strong degree of penetration into the UK academic community [17]. This is the first systematic national survey published on astrobiology activity.…”
Section: Introductionmentioning
confidence: 97%
“…Being an important and also popular subtopic of astrobiology, exoplanets often appear in the popularization related issues [9][10][11] and in the education. Although this hot topic is in the focus, only images were used to visualize the size of these bodies, and the methods often lacks the visualization of distances proportional to the real stellar and planet sizes.…”
Section: Introductionmentioning
confidence: 99%